Yuri O. answered • 02/11/21

16 years online, 464 former SAT problems drilled down

cos(A + B) = cos(A)cos(B) - sin(A)sin(A)

cos(A - B) = cos(A)cos(B) + sin(A)sin(A)

Adding equations:

(1/2)(cos(A + B) + cos(A - B)) = cos(a)cos(A)

=====================================

**cos(a)cos(A) = (1/2)(cos(A + B) + cos(A - B))**

cos(2θ)cos(6θ) = (1/2)(cos(8θ) + cos(-4θ))

Note that cos(-4θ) = cos(4θ) ← even identity

Therefore,

**cos(2θ)cos(6θ) = (1/2)cos(8θ) + (1/2)cos(4θ)**

Yuri O.

02/12/21

Matthew B.

thank you very much this was very helpful and i really appreciate it!02/12/21